Glioblastoma microenvironment and its reprogramming by oncolytic virotherapy - Qi, Zhongbing; Long, Xiangyu; Liu, Jiyan; Cheng, Ping (Frontiers in Cellular Neuroscience, 2022)
Glioblastoma (GBM), a highly aggressive form of brain tumor, responds poorly to current conventional therapies, including surgery, radiation therapy, and systemic chemotherapy. The reason is that the delicate location of the primary tumor and the existence of the blood-brain barrier limit the effectiveness of traditional local and systemic therapies. The immunosuppressive status and multiple carcinogenic pathways in the complex GBM microenvironment also pose challenges for immunotherapy and single-targeted therapy. With an improving understanding of the GBM microenvironment, it has become possible to consider the immunosuppressive and highly angiogenic GBM microenvironment as an excellent opportunity to improve the existing therapeutic efficacy. Oncolytic virus therapy can exert antitumor effects on various components of the GBM microenvironment. In this review, we have focused on the current status of oncolytic virus therapy for GBM and the related literature on antitumor mechanisms. Moreover, the limitations of oncolytic virus therapy as a monotherapy and future directions that may enhance the field have also been discussed.